MAKNA RUWAYBIDAH DAN RUMUSAN ETIKA KOMUNIKASI DI ERA DIGITAL - Muna, Moh. Nailul (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2019)
This study aims to discuss the ethics of public communication in a digital age, based on the hadith perspective. It is based on the poor ethics of communication in society, which leads to the emerge of SARA, hoaxes, and politicization of religion. The article addresses prophetic traditions concerning ruwaybid}ah that could provide values ??on the norms of communication. Based on the lexical meaning, the word ruwaybid}ah means people who are weak towards noble matters. Muhammad?s description through the editorial ?fools who meddled in community affairs? has a close relation to the cause of social inequality at that time. Through a socio-historical approach, it argues that anyone who does not have capabilities in a particular field and tries to impose his or her incapacity, they could belong to the ruwaybid}ah category. Further, this study attempts to formulate key important principles of today?s digital age communication based on the hadith.